Beamspace MUSIC Algorithm based on Space-time Array Signal Model. (August 2019) - Yang, B; Yang, B; Wang, C; Shen, H X
Abstract: This paper is devoted to the direction-of-arrival (DOA) algorithm in the moving array scenario. A beamspace MUSIC algorithm based on space-time signal model is proposed to cope with this scenario. First, the DOA information contained in Doppler shift is used to combine with the array spatial information, thus constructing a space-time signal model. Second, allowing for the considerable dimension and complexity of the space-time model, we transform the array sensor data into beamspace to reduce the computation load. The introduction of Doppler information leads to significant enhancement in algorithm performance. Simulation results demonstrate the promotion of proposed algorithm.